2022
DOI: 10.1186/s13104-022-05987-4
|View full text |Cite
|
Sign up to set email alerts
|

Using ZINC08918027 inhibitor to determine Aurora kinase-chromosomal passenger complex isoforms in mouse oocytes

Abstract: Objective Miscarriages affect 10% of women aged 25–29, and 53% of women over 45. The primary cause of miscarriage is aneuploidy that originated in eggs. The Aurora kinase family has three members that regulate chromosome segregation. Therefore, distinguishing the roles of these isoforms is important to understand aneuploidy etiology. In meiosis, Aurora kinase A (AURKA) localizes to spindle poles, where it binds TPX2. Aurora kinase C (AURKC) localizes on chromosomes, where it replaces AURKB as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The mammalian genome encodes three members: Aurora kinase A (AURKA), Aurora kinase B (AURKB), and Aurora kinase C (AURKC). AURKA mainly localizes with aMTOCs [12, 13], with a minor chromosomal population [14]. Through mouse knockout studies, we found that although each isoform is important for female fertility and oocyte meiosis, only AURKA is necessary and sufficient for fertility [1, 2].…”
Section: Resultsmentioning
confidence: 99%
“…The mammalian genome encodes three members: Aurora kinase A (AURKA), Aurora kinase B (AURKB), and Aurora kinase C (AURKC). AURKA mainly localizes with aMTOCs [12, 13], with a minor chromosomal population [14]. Through mouse knockout studies, we found that although each isoform is important for female fertility and oocyte meiosis, only AURKA is necessary and sufficient for fertility [1, 2].…”
Section: Resultsmentioning
confidence: 99%
“…The different strains of mice used in this work were generated by mating of floxed Aurka (C57BL/6N) (Aurka f/f ) mice or Aurkb fl/fl Gdf9-Cre mice with double knockout mice for AURKB and AURKC (C57BL/6J, 129/Sv) (Aurkb f/f , Aurkc −/− , Gdf9-Cre mice (BC-KO), described before. 18 , 19 , 22 After several rounds of mating, we isolated animals that were Aurka f /f , Aurkb f /f , and Gdf9-Cre mice (AB-KO), and Gdf9-Cre mice (ABC-KO). Moreover, we also used animals Aurkb f /f , Aurkc −/− , and Gdf9-Cre mice (BC-KO).…”
Section: Methodsmentioning
confidence: 99%
“…AURKA concentrates at aMTOCs, 16 , 17 and also has a minor chromosomal population. 18 AURKB is mainly cytoplasmic and around the spindle, and AURKC is localized at the interchromatid axis of meiosis I bivalents, at KTs, and at spindle poles. 19 Through mouse knockout studies, we found that although each isoform is important for female fertility and oocyte meiosis, only AURKA is essential for fertility.…”
Section: Introductionmentioning
confidence: 99%